Relationship between Organizational Quiet Behaviors in Nurses and Hospital and Nurse Characteristics - Noora Nasser Alqahtani; Munera Hassan Alqahtani; Nora Ayed Alqahtani; Ahlam Abdullah Alqahtani; Shahad Abdullah Alqahtani; Abeer Ayed Alharthi; Samar Ayed Alqahtani; Aisha Abdulqader Bakri; Haya Nasser Alqahtani; Agab Mohammad Alqahtani; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Organizational silence among nurses is a critical issue that can have significant implications for patient safety and care quality. This study aimed to assess Relationship between organizational quiet behaviors in nurses and hospital and nurse characteristics. A cross-sectional study was conducted, involving 624 licensed registered nurses . The Organizational Silence Behavior Scale (OSBS) was used to measure organizational silence. Descriptive statistics, t-tests, Anova, correlation analysis, and multiple linear regression were employed for data analysis. The results indicated a moderate level of overall organizational silence, with prosocial silence being the most prevalent type. Nurses’ years of experience, facility size, and urban location were found to be significant predictors of organizational silence. The findings highlight the need for nursing management to create a work environment that encourages open communication and supports nurses in speaking up about patient safety concerns. Strategies such as implementing reporting systems, providing assertiveness training, and promoting interprofessional collaboration can help mitigate organizational silence and improve patient outcomes.